Residential environments, alcohol advertising, and initiation and continuation of alcohol consumption among adolescents in urban Taiwan: A prospective multilevel study. (December 2016) - Chen, Yen-Tyng; Cooper, Hannah L.F.; Windle, Michael; Haardörfer, Regine; Crawford, Natalie D.; Chen, Wei J.; Chen, Chuan-Yu
Abstract: Background: Research indicates that place characteristics and the media environment are important contextual determinants of underage drinking behaviors in Western countries, but it is unknown whether these exposures influence adolescent alcohol consumption outside Western contexts, including in Asia׳s emerging global alcohol markets. Guided by the social ecological framework, we prospectively investigated the influences of place characteristics and alcohol advertising on initiation and continuation of alcohol consumption among adolescents in Taipei, Taiwan. Methods: Data on individual-level characteristics, including alcohol use behaviors and perceived exposure to alcohol advertising, were obtained from two waves of a longitudinal school-based study through a stratified probability sampling method in 2010 (Grade 7/Grade 8, aged 13-14 years old) and 2011-2012 (Grade 9, aged 15 years old) from 1795 adolescents residing in 22 of 41 districts in Taipei. Data on district-level characteristics were drawn from administrative sources and Google Street View virtual audit to describe districts where adolescents lived at baseline. Hierarchical generalized linear models tested hypotheses about the associations of place characteristics and perceived alcohol advertising with underage drinking, with stratification by baseline lifetime alcohol consumption. Results: Among alcohol-naïve adolescents, lower district-level economic disadvantage, a higher proportion of betel nut kiosks (a relatively unregulated alcohol source) compared to off-premises alcohol outlets, and exposure to television-based alcohol advertising predicted increased likelihood of alcohol initiation at one-year follow-up. Among alcohol-experienced adolescents, greater spatial access to off-premises alcohol outlets, and lower access to metro rapid transportation (MRT) and to temples were found to predict a subsequent increased likelihood of continued alcohol use. Parental drinking moderated the relationship between district-level violent crime and initiation of alcohol consumption. Conclusions: These findings suggest that local social economic status, alcohol access, and institutional resource and individual media exposure affect underage drinking behaviors in Taiwan. We discuss potential public health implications for place-based interventions. Future research on place, media, and adolescent alcohol consumption in Asian contexts is warranted. Highlights: This is one of the first cohort studies of place, media and youth drinking in Asia. We used a novel spatial measure of unregulated alcohol outlets in Taiwan. Greater spatial access to betel nut kiosks predicted youth alcohol initiation. Lower place-based economic disadvantage predicted youth alcohol initiation. Lower spatial access to institutional resources predicted youth continued drinking.